2019
DOI: 10.1021/acs.energyfuels.9b00164
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on CO2 Sweep Volume during CO2 Huff-n-Puff Enhanced Oil Recovery Process in Shale Oil Reservoirs

Abstract: CO2 huff-n-puff has been proven to be the most effective enhanced oil recovery (EOR) method in shale oil reservoirs. The injected CO2 will replenish reservoir energy and penetrate the reservoir matrix to extract oil. However, the CO2 sweep volume during the huff-n-puff process has not been accurately evaluated by existing studies. In this paper, the CO2 sweep volume was investigated through experimental and numerical simulation methods. In the experimental study, the CO2 sweep areas were depicted by X-ray comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 75 publications
0
45
0
Order By: Relevance
“…In an effort to replenish reservoir pressure and improve oil recovery, authors such as Sheng and Chen investigated confirmed conventional field injection processes, including gas flooding schemes (e.g., continuous CO 2 injection and water-alternating-CO 2 (CO 2 –WAG) flooding) in shale oil reservoirs. Unfortunately, those approved methods were found to consume a considerable amount of gas to recover the desired oil volume . Another persistent challenge to researchers is that the gas applied into a tight formation is subjected to an early breakthrough, especially in densely fractured reservoirs, thus causing poor oil displacement .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to replenish reservoir pressure and improve oil recovery, authors such as Sheng and Chen investigated confirmed conventional field injection processes, including gas flooding schemes (e.g., continuous CO 2 injection and water-alternating-CO 2 (CO 2 –WAG) flooding) in shale oil reservoirs. Unfortunately, those approved methods were found to consume a considerable amount of gas to recover the desired oil volume . Another persistent challenge to researchers is that the gas applied into a tight formation is subjected to an early breakthrough, especially in densely fractured reservoirs, thus causing poor oil displacement .…”
Section: Introductionmentioning
confidence: 99%
“…The cost of pilot studies is another existing challenge which is in excess of several million U.S. dollars, compared with laboratory research that can be performed at significantly lower costs. Researchers initiating valuable attempts to increase oil productivity of shale/tight oil reservoirs include the reports given in refs , , , , , , , , . Most of the authors confirmed the success of the H-n-P application; however, they disagreed over the influence of some crucial mechanisms and key parameters, because of the lack of actual field data.…”
Section: Introductionmentioning
confidence: 99%
“…The above mentioned mechanisms may play important roles in tight (e.g., Middle Bakken formation) or conventional reservoirs, where gas is relatively easier to diffuse into the matrix and to make contact with oil. Recent studies visualized the gas sweep volume in ultra-tight shale plugs by using CT images [33,58], indicating that gas could make contact with the oil that is trapped in nanosized pores. Furthermore, the nanoconfinement effect may influence the estimations of MMP and alter the fluid properties, so the inclusion of capillary pressure effect and the shift in critical properties results in more accurate recovery prediction [52,54].…”
Section: Gas Flooding Performance Evaluationmentioning
confidence: 99%
“…The interaction of carbon dioxide with formation fluid has led to reduce oil viscosity and enhance the mobility ratio. The profound impact of crucial parameters such as temperature, pressure, carbon dioxide soaking time, and core stimulation on the oil recovery enhancement should be taken into consideration before performing recovery processes (Zhang et al, 2019;Li et al, 2019;Alfarge et al, 2018;Pranesh, 2018).…”
Section: Introductionmentioning
confidence: 99%